A complex network analysis of sustainable research partnerships; evidence from a developing country. (2019) - Yao, Hongxing; Ankomah-Asare, Evans Takyi; Schwinger, Eyram Kojo; Akuamoah, Worlanyo Savior; Dankyi, Alex Boadi
The discrete and continuous probability of co-author network sustainability was assessed based on modified Bass-SIR innovation diffusion models. The implications of industry and government funding of research partnership was empirically tested, using data from a specialised research institute. We conclude that development and sustainability of research partnerships is critically dependent on the formation of co-author research networks and their influence on author successes. Thus when research centres fail to maintain co-author networks and authoring rates, the research institutions that authors belong to will eventually become unproductive and likely to suffer partnership attrition.